2008
DOI: 10.1212/01.wnl.0000312378.94737.45
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of young-adult amyotrophic lateral sclerosis

Abstract: Our findings show that young-adult amyotrophic lateral sclerosis with the predominant upper motor neuron phenotype represents a distinctive clinical variant characterized by a unique clinical pattern, longer survival, and male prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 24 publications
4
59
0
3
Order By: Relevance
“…Juvenile ALS is defined as ALS with age at onset before 25 years, and the course of progression is generally slower than in other forms of ALS. 15,16 poor prognosis. [17][18][19] In some forms of ALS, such as the SETX-associated ALS type 4, the phenotype is so atypical that some authors suggest they should be considered as separate disease entities rather than ALS.…”
Section: Age At Onsetmentioning
confidence: 99%
See 1 more Smart Citation
“…Juvenile ALS is defined as ALS with age at onset before 25 years, and the course of progression is generally slower than in other forms of ALS. 15,16 poor prognosis. [17][18][19] In some forms of ALS, such as the SETX-associated ALS type 4, the phenotype is so atypical that some authors suggest they should be considered as separate disease entities rather than ALS.…”
Section: Age At Onsetmentioning
confidence: 99%
“…20,21 60% of patients with disease onset between 20 and 40 years of age have predominantly upper motor neuron involvement, and relatively few of these patients (15%) have bulbar-onset disease. 15 Older age at onset is associated with decreased likelihood of upper motor neuron involvement (20%), increased probability of bulbar onset (some studies report up to 50% with onset after 80 years of age), and poor prognosis. 9,22,23 Onset after 80 years is associated with a particularly short survival.…”
Section: Age At Onsetmentioning
confidence: 99%
“…Except for the rare juvenile form (especially the very aggressive fused in sarcoma (FUS) gene mutation form [9]) the age range for developing ALS is quite broad, between 45 and 60 years [10]. The progressive atrophy and loss of upper (corticospinal) and lower (spinal and bulbar) specialized neurons lead to muscle atrophy, weakness and spasticity, and rapidly to paralysis [11].…”
mentioning
confidence: 99%
“…It is unclear which, if any, of the clinical variables are important for predicting survival. Previous studies of ALS populations identified several negative prognostic factors, [1][2][3][4][5][6][7][8][9][10][11][12][13] including older age at onset, female sex, and bulbar onset. As there is so much inconsistency in the published literature regarding the relative importance of prognostic factors, clinicians are challenged to provide a well-reasoned prognosis to newly diagnosed patients.…”
mentioning
confidence: 99%